Aerosols modification with H2O2 reduces airborne contamination by dental handpieces. Issue 1 (1st January 2021) - Ionescu, Andrei Cristian; Brambilla, Eugenio; Manzoli, Lamberto; Orsini, Giovanna; Gentili, Valentina; Rizzo, Roberta
ABSTRACT: Objective : We designed an in vitro study to evaluate the efficiency of an 0.5 vol% hydrogen peroxide-based spray in reducing Coronavirus 229E spread during a conventional dental procedure. Methods : A class III cabinet-like chamber was custom-built, using phantoms for both patient and operator. A suspension of HCoV-229E in artificial saliva having a similar viral load to SARS-CoV-2 asymptomatic patients was inoculated inside the patient's phantom mouth. A 10 s-lasting dental procedure was performed using an aerosol-generating air-turbine, with or without high-volume evacuation (HVE). The effect of 0.5 vol% H2 O2 cooling spray in reducing viral loads was tested. Viral presence on the operator phantom was assessed by Real-Time quantitative PCR on the mask's outer surface, on the phantom's forehead, and inside its mouth. Results : When the H2 O2 cooling spray was used, as compared to the conventional spray, viral loads were significantly lower on all tested sites, falling below the detection limit. Viral loads did not significantly change in any tested site when HVE was used. Conclusion : The use of 0.5 vol% H2 O2 cooling spray by dental handpieces drastically reduced the possibility of coronaviruses spread during aerosol-generating dental procedures. This strategy deserves further consideration among the preventive measures to be adopted during the SARS-CoV-2 pandemic.